Lamium bilgilii (Lamiaceae), a new species from South-western Turkey (Burdur-Muğla) - Celep, Ferhat (Phytotaxa, 2017)
Lamium bilgilii Celep (Lamiaceae) is here described as a new species. It is confined to Altİnyayla (Dirmil), Burdur-Muğla border, in South-western Turkey. Lamium bilgilii differs from L. garganicum by its denser, long eglandular villous indumentum accompanied by short glandular hairs on the stem, leaf, inflorescence axis, calyx and corolla; larger corolla (40–52 mm), humped, and largely ventricose corolla tube and wider corolla throat. IUCN red list category, distribution map, notes on biogeography and ecology of the new species are also given.